posted by Tamia on .
Please help to find x, y
6x+y=11 (adding the equation)
__________ (-y and +y will be 0)
Taking variables to one side
substitute this value of x in equation 2
(x=2)and (y=-1) is the solution of the given equation.
Instead of miley's suggestion, do the following:
Take the value of y in the first formula and substitute it for y in the second formula. Solve the second formula for x.
y=8x-17 (Value of y)
Once x is found, solve for y in the second formula. Check by inserting both values into the first formula.
I hope this helps much more. Thanks for asking.
Question no 2
5x-2y=17 eq 1
2x+3y=3 eq 2
multiply eq 1 by 3
15x-6y=51 eq 3
Now multiply eq 2 by 2
4x+6y=6 eq 4
19x =57 (adding both the equations)
substitute this value of x in eq 2
(x=3) and (y=-1) is the solution of the given equation.
x and the co-effecient cannot be subtracted so the substitution by adding is better
hey tamia can i know by which method are you solving the equation ?
the you is for my and how that the line of best fit equation is appropriate, mentioning both the slop and y-intercept in your response